KAJIAN ADAPTASI VARIETAS UNGGUL BARU PADI DAN TINGKAT SERANGAN ORGANISMA PENGGANGGU TANAMAN PADA DUA LOKASI SENTRA PADI DI PROVINSI GORONTALO - Warda Warda (Biocelebes, 2018)
Averaged productivity of paddy in Gorontalo on 2009 was 4.56 t / ha. The productivity of paddy plants is lower compared with the potential yields that can produce 8.0 t / ha. One of the causing problems of low productivity is the attack of pests. Paddy plants have many pests, primary and non-primary. Litbang has released many new superior varieties (NSV) of paddy rice with various advantages of each variety, especially resistance to certain pests. However, some varieties do not show resistance to pests in certain agroecosystems. The objective of the assessment was to obtain resistant or tolerant tolerant paddy field NSV in the Gorontalo agroecosystem. The assessment consisted of two experiments ie : (1) Assessment of NSV resistance to pest attack and (2) Survey of the type and level of rice pest populations in the two selected districts. The study used Randomized Block Design and survey methods in Kabupaten Gorontalo and Boalemo from January to December 2012. The paddy field NSVs in the test were Inpari 2, Inpari 3, Inpari 4, Inpari 6, Inpari 7, Inpari 9, Inpari 10 and Inpari 13 and Ciherang and memberamo as control / comparison. Inpari 4 and Inpari 10 varieties tend to have resistance to pests and have high yield potential in the field. The dominant and potentially destructive pests in each plant stadia are stem borer, crackle, HPP, grayak caterpillar and earthen bundle. The natural enemies that are dominant in helping balance natural ecosystems are spiders and telenomus.